2020
DOI: 10.1128/msystems.00138-20
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of 16S rRNA Microbial Data Identified Distinctive and Predictive Microbiota Dysbiosis in Colorectal Carcinoma Adjacent Tissue

Abstract: As research focusing on the colorectal cancer fecal microbiome using shotgun sequencing continues, increasing evidence has supported correlations between colorectal carcinomas (CRCs) and fecal microbiome dysbiosis. However, large-scale on-site and off-site (surrounding adjacent) tissue microbiome characterization of CRC was underrepresented. Here, considering each taxon as a feature, we demonstrate a machine learning-based method to investigate tissue microbial differences among CRC, colorectal adenoma (CRA), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 48 publications
1
29
0
1
Order By: Relevance
“…11), indicating the non-invasive clinical screening tests could be used as complementary characteristics of gut microbiota for early screening of adenoma. Recently, a 16s rRNA analysis showed that microbiome dysbiosis in adjacent tissues could discriminate colorectal adenomas from healthy controls effectively(13), providing a new insight for following research of adenoma biomarkers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…11), indicating the non-invasive clinical screening tests could be used as complementary characteristics of gut microbiota for early screening of adenoma. Recently, a 16s rRNA analysis showed that microbiome dysbiosis in adjacent tissues could discriminate colorectal adenomas from healthy controls effectively(13), providing a new insight for following research of adenoma biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, current knowledge of the associations between microbiome and biomarkers for colorectal adenoma early-detection is poor as well. Only a few studies have investigated the microbial alterations in colorectal adenoma(4, 7, 11-13). However, a substantial variation exists among microbial makers in these studies, and its cause could be various biological factors influencing gut microbiome composition and inconsistent processing of microbial sequencing data.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(37) Since better understanding of the role of gut microbiota in either colon adenoma progression or CRC carcinogenesis could provide promising new directions to either prevention or treatment, the discovery of novel biomarkers of the gut microbiome might be of outmost importance. (38)(39)(40) Microorganisms affected the onset and progression of CRC via acceleration of chronic mutagenic inflammation, the biosynthesis of genotoxins that interfere with cell cycle regulation, the production of toxic metabolites, activation of carcinogenic diet compounds, and robust oxidative genotoxic stress, by which altered gut microbiota may allow the outgrowth of bacterial populations that induce genomic mutations or exacerbate tumor-promoting inflammation, concluding large metagenomic studies in CRC-associated microbiome signature significantly tells fundamental role of intestinal microbiota in adenoma-carcinoma sequence. (41) As like in the current investigation denoted in advanced colon adenoma, S. bovis, Helicobacter pylori, B. fragilis, E. faecalis, C. septicum, Fusobacterium spp., and Escherichia coli were reported to be pathogen responsible for colon tumorigenesis including adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%